Experimental Scaling Challenges of Air Turbines for Oscillating Water Column Wave energy converters (Proceedings of the European Wave and Tidal Energy Conference, 2025)
One of the key aspects of advancing research in marine renewable energy is the ability to conduct experiments with scaled physical models. The reliability of experimental data is crucial for improving the accuracy of model representations and enhancing the precision in predicting extractable power and plant performance.This paper focuses on the experimental representation of a fixed Oscillating Water Column (OWC) equipped with an impulse turbine applied as a power take-off. The impulse turbine is experimentally represented by an orifice of fixed diameter. One of the most significant challenges in OWC experiments is the inability to simultaneously match the scaling of hydrodynamics and aerodynamics in the air chamber due to the mismatch of Reynolds numbers under Froude scaling. To address the limitations posed by the small scale of the prototype, this study focuses on calculating the air flow rate of the air turbine while accounting for the appropriate flow regime, transitioning between laminar and turbulent conditions. Accordingly, it proposes a methodology for accurately representing the experimental air flow rate through the air turbine, addressed to the scale of the model.Given that the air flow rate through an orifice depends on air pressure, it is essential to calibrate both the discharge coefficient and the power dependence on pressure. The comparison with experimental data identifies the coefficients that best fit the air flow regime through the orifice and accurately represent the scaled model. The results show the fitting of the experimental air flow rate with theoretical predictions based on modeling the orifice as a valve. Best-fit discharge coefficients and power-pressure dependencies are applied to calculate the flow rate for various area ratios and wave scenarios. The limits given by the scale are discussed together with the validity of the theoretical assumptions for the different cases. The corrected air flow rate is subsequently used to evaluate the pneumatic power of the wave energy converter. Differences in pneumatic power between the expected and evaluated values are quantified to assess the error introduced by assumptions in air flow rate calculations.The findings underscore the importance of accurately representing the physics of air turbines in small-scale prototypes, where the match of Reynolds number cannot be verified. The results help assess the reliability of estimated OWC performance and highlight the impact of assumptions on the accuracy of the predictions based on a scaled model representation.